Expectations around university and career choice. An analysis of atypical cases of graduates and students in the finishing phase who are first generation university students (Praxis Educativa, 2024)
In this paper we analyse the expectations regarding university studies and career choice of first-generation university students and graduates. Our interest in this particular population is due to the fact that they are atypical cases. The theoretical perspective is the relationship with knowledge and dispositionalist and contextualist sociology. The methodology is qualitative and we used in-depth interviews with a sample of 35 students from three degree courses at the National University of La Plata. The families and the school experience were central in the construction of expectations, while the choice of career was defined on the basis of the transit through secondary school, in the university experience itself as well as in other non-school environments.
Keywords: expectations; career choice; first generation of university students; relationship with knowledge; inequalities.